Aplastic bone marrow in dogs (Revista de Ciências Agroveterinárias, 2010)
Aplastic bone marrow (also known as aplastic anemia) is relatively rare in small animals. It is characterized by pancytopenia in the peripheral blood and a three linage bone marrow hypoplasia (erythroid, myeloid and megakaryocytic), resulting in hematopoietic cells replacement by fat tissue. Aplastic bone marrow can also be classified as acute or chronic, according to its presentation and evolution of the cytopenias in the peripheral blood. Among the causes for aplastic bone marrow that lead to stem cells or progenitor cells damage there are the infectious diseases, drugs, toxins and radiation. There are some cases where it is not possible to identify its origin. Then, the aplasia is defined as idiopathic by exclusion. For such diagnosis, it is necessary to rule out other causes of pancytopenia associated to myelophtisis, such as leukemias and myelofibrosis, myelodysplastic syndrome (MDS), myelonecrosis, pure red cell aplasia and hemophagocytic syndrome. Bone marrow aspirate biopsies are performed more frequently than core biopsies in veterinary medicine, and it is fundamental to evaluate alterations of bone marrow. Bone marrow core biopsy provides a more accurate way of evaluating marrow cellularity and examining for metastatic neoplasia. Besides the therapy directed to the primary causes, aplastic bone marrow treatment is limited and the prognosis is usually unfavourable.
Keywords: Aplastic bone marrow; Aplastic anemia; Dog; Pancytopenia; Nonregenerative anemia.